Natural Convection Heat Transfer in Arc Shape Wall Porous Cavity Filled with Nano-Fluid - Ismael, Muneer A.; AL-Mayahi, Huda A.; Jawad, Ihsan N. (Basrah Journal for Engineering Sciences, 2014)
Natural convection heat transfer in porous cavity with arc shape wall filled with nanofluid is studied numerically. The right arc shape wall of the cavity is heated at constant temperature (Th) while the left wall is kept cold at constant temperature (Tc), and the other horizontal walls are thermally insulated. The governing equations of the heat transfer and nanofluid flow are solved Flex PDE software. A temperature independent nanofluids properties models are adopted. The investigated parameters are the nanoparticles volume fraction Ø= (0-0.2), Rayleigh number Ra (10-1000) and arc center Ce (1-∞). The results are presented by contour of streamlines, isotherms and the average Nusselt number. The results have showed that the average Nusselt number decreases with increasing Ce and increases with increasing Ra and Ø.